Acids and bases : solvent effects on acid-base strength - Cox, Brian G. (Oxford University Press, 2013)
This volume seeks to enhance our understanding of acids and bases by reviewing and analysing their behaviour in non-aqueous solvents. The behaviour is related where possible to that in water, but correlations and contrasts between solvents are also presented.